Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. (5th October 2011) - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A.; Ammadeo, A.; Gattorno, M.; Not, T.; Lepore, L.; Crovella, S.
Abstract : Human glycolytic enzyme α -enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti- α -enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.